2200. Impact of COVID-19 Pandemic on Influenza-like Illness (ILI) Experience among Healthcare Workers in Military Treatment Facilities. (15th December 2022) - Liberg, Ryan; Schofield, Christina; Richard, Stephanie A; Collins, Limone; Spooner, Christina; Seshadri, Srihari; Ganesan, Anuradha; Campbell, Wesley R; Hrncir, David; Lalani, Tahaniyat; Warkentien, Tyler; Mende, Katrin; et al.
Abstract: Background: Healthcare workers (HCWs) are at heightened risk of exposure to respiratory pathogens, and occupy an important epidemiologic position in the COVID-19 pandemic. PAIVED, a multicenter, multiservice study assessing influenza vaccine effectiveness in the Department of Defense over four consecutive influenza seasons (2018-22), provides an opportunity to describe influenza like illness (ILI) experience and assess the impact of SARS-CoV-2 in HCWs compared to non-HCWs. Methods: PAIVED participants were randomized to receive either egg-based, cell-based, or recombinant-derived influenza vaccine and then surveyed weekly for ILI. At enrollment, participants provided key demographic data including whether they were HCWs with direct patient contact. ILI was defined a priori as 1) having cough or sore throat plus 2) feeling feverish/having chills or having body aches/fatigue. Participants with ILI completed a symptom diary for seven days and submitted a nasal swab for pathogen detection. Study recruitment was conducted from September-January over four consecutive years. Results: Of 13188 eligible participants enrolled, 4819 (36%) were HCWs. Overall, HCWs were more likely to be female (43% vs 31%), active duty military (86% vs 69%), and to identify as white (61% vs 56%). HCWs more commonly reported ILI than non-HCWs (25% vs 21%, p< 0.01). Of those experiencing ILI, SARS-CoV-2 was identified in a higher proportion of HCWs than non-HCWs (17% vs 12%, p< 0.01). Influenza was isolated in similar proportion of HCWs and non-HCWs (5% vs 4%). Each group reported similar ILI duration and severity (p< 0.01). Conclusion: In a prior analysis of the 2019-20 PAIVED season, HCWs were more likely than non-HCWs to report ILI, have shorter illness duration, and isolate influenza A (H1N1). The propensity for HCWs to report ILI persisted over the four years. While SARS-CoV-2 emerged as a major pathogen in both groups, HCWs were more likely to have it identified as a cause of ILI, suggesting increased risk of symptomatic SARS-CoV-2 in our HCW population. Influenza incidence was lower than that of SARS-COV-2, and did not differ between HCWs and non-HCWs. Mean duration of illness did not differ between groups over four years; this equalization may relate to the higher incidence of SARS-CoV-2 in HCWs. Disclosures: Jitendrakumar Modi, MD, GlaxoSmithKline: I am a paid speaker for GSK. I do not speak for their flu brand. Timothy Burgess, MD, MPH, AstraZeneca: The HJF, in support of the USU IDCRP, was funded to conduct or augment unrelated Phase III Mab and vaccine trials as part of US Govt. COVID19 response.